Clinicopathological characteristics, staging classification, and survival outcomes of primary malignant melanoma of the esophagus. Issue 4 (19th December 2017) - Sun, Haiyan; Gong, Lei; Zhao, Gang; Zhan, Hongdian; Meng, Bin; Yu, Zhentao; Pan, Zhanyu
Abstract : Background: Primary malignant melanoma of esophagus (PMME) is a remarkably rare and highly aggressive tumor. Studies related with clinicopathological findings, staging classification, and clinical outcomes are lacking. Methods: We reviewed 21 cases of PMME at the Tianjin Medical University Cancer Institute and Hospital from January 2002 to February 2017. Results: Nineteen patients (90.48%) presented a history of dysphagia for months, and two (9.52%) experienced retrosternal pain. Histologically, tumors were composed of atypical melanocytes with melanocytosis surrounding the tumor. The overall survival was 1‐40 months, with the median time of 10 months. The mucosal staging classification for upper aerodigestive tract showed better distribution of overall survival with different stages than that of the American Joint Commission on Cancer staging classification for esophagus, but without statistical difference. Both the clinical and pathological characteristics were not highly consistent with overall survival. Conclusions: PMME is a considerably aggressive tumor with poor prognosis. The staging classification of mucosal melanoma of the upper aerodigestive tract may be a good option for PMME patients.